2015
DOI: 10.1073/pnas.1423356112
|View full text |Cite
|
Sign up to set email alerts
|

CD169+macrophages are sufficient for priming of CTLs with specificities left out by cross-priming dendritic cells

Abstract: Dendritic cells (DCs) are considered the most potent antigen-presenting cells (APCs), which directly prime or cross-prime MHC I-restricted cytotoxic T cells (CTLs). However, recent evidence suggests the existence of other, as-yet unidentified APCs also able to prime T cells. To identify those APCs, we used adenoviral (rAd) vectors, which do not infect DCs but selectively accumulate in CD169 + macrophages (MPs). In mice that lack DCs, infection of CD169 + MPs was sufficient to prime CTLs specific for all epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 38 publications
6
110
0
Order By: Relevance
“…Moreover, although it has been reported that DT treatment of CD11c. DTR transgenic mice may also partially ablate macrophages, 20,21 the other important professional APC in vivo, we treated CD11c.DTR transgenic mice with LClo, a compound that upon selective phagocytosis by macrophages kills the cells by apoptosis, 19 and in the spleen ablates particularly the marginal zone macrophages and metallophilic macrophages, considered the predominant APCs, in the spleen. 22 Again, upon injection, CIITA-tumor cells could be rejected or strongly retarded in their growth with superimposable behavior as the one observed in liposomal-untreated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although it has been reported that DT treatment of CD11c. DTR transgenic mice may also partially ablate macrophages, 20,21 the other important professional APC in vivo, we treated CD11c.DTR transgenic mice with LClo, a compound that upon selective phagocytosis by macrophages kills the cells by apoptosis, 19 and in the spleen ablates particularly the marginal zone macrophages and metallophilic macrophages, considered the predominant APCs, in the spleen. 22 Again, upon injection, CIITA-tumor cells could be rejected or strongly retarded in their growth with superimposable behavior as the one observed in liposomal-untreated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of DT in CD11c-DTR mice efficiently depletes DCs but also causes depletion of the marginal zone metallophilic macrophages (11,12), which are important to prevent spread of LCMV and T cell exhaustion (13). In contrast, the intrinsic DTA expression in DCs of DDC mice causes selective deletion of classical DCs, plasmacytoid DCs, and Langerhans cells, but not macrophages (12,14).Therefore, DDC mice can be regarded as a more specific model to study the role of DCs for the immune response to LCMV.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, diphtheria toxin (DT)-induced ablation of DCs in CD11c-DTR mice resulted in an impaired CD8 T cell response to LCMV (10). However, these results were not conclusive because later studies showed that DT treatment also ablated marginal zone metallophilic macrophages in the spleen (11,12). These macrophages were found to be critical for limiting the spread of LCMV to other organs and to prevent exhaustion of CD8 T cells (13).…”
Section: Ymphocytic Choriomeningitis Virus (Lcmv)mentioning
confidence: 99%
“…Studies in murine systems have shown that CD169 C Mf contribute to antigen retention and cross-presentation of antigens to CD8 C T cells in the LN, thereby functioning as powerful APCs that significantly contribute to CTL responses. 21,23,26 The mechanism of generating CD169 C CD8 C T cells is presently unknown. T lymphocytes located adjacent to CD169 C Mf have been shown to be stained for CD169 due to blebs from CD169 C Mf undergoing fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] A recent study demonstrated that CD169 C Mf could effectively generate CTL responses by cross-priming CD8 C T cells, which in turn, conferred immunity against re-exposure to the malignant cells. 26 The expression of CD169 in tumor-draining LN and its association with survival in CRC patients has been recently reported 27 ; however, the specific composition and function of CD169 C cells in tumor-draining LNs of cancer patients remain largely unknown. In the current study, we addressed this issue in CRC and identified a novel T cell subset, CD169 C CD8 C T cells.…”
Section: Introductionmentioning
confidence: 99%